Genetic Nurture Effects on Type 2 Diabetes Among Chinese Han Adults: A Family-Based Design - Xiaoyi Li; Zechen Zhou; Yujia Ma; Kexin Ding; Han Xiao; Tao Wu; Dafang Chen; Yiqun Wu (Biomedicines)
Background/Objectives: Genes and environments were transmitted across generations. Parents’ genetics influence the environments of their offspring; these two modes of inheritance can produce a genetic nurture effect, also known as indirect genetic effects. Such indirect effects may partly account for estimated genetic variance in T2D. However, the well-established specific genetic risk factors about genetic nurture effect for T2D are not fully understood. This study aimed to investigate the genetic nurture effect on type 2 diabetes and reveal the potential underlying mechanism using publicly available data. Methods: Whole-genome genotyping data of 881 offspring and/or their parents were collected. We assessed SNP-level, gene-based, and pathway-based associations for different types of genetic effects. Results: Rs3805116 (β: 0.54, p = 4.39 × 10−8) was significant for paternal genetic nurture effects. MRPS33 (p = 1.58 × 10−6), PIH1D2 (p = 6.76 × 10−7), and SD1HD (p = 2.67 × 10−6) revealed significantly positive paternal genetic nurture effects. Five ontologies were identified as enrichment in both direct and indirect genetic effects, including flavonoid metabolic process and antigen processing and presentation via the MHC class Ib pathway. Two pathways were only enriched in paternal genetic nurture effects, including the transforming growth factor beta pathway. Tissue enrichment of type 2 diabetes-associated genes on different genetic effect types was performed using publicly available gene expression data from the Human Protein Atlas database. We observed significant gene enrichment in paternal genetic nurture effects in the gallbladder, smooth muscle, and adrenal gland tissues. Conclusions: MRPS33, PIH1D2, and SD1HD are associated with increased T2D risk through the environment influenced by paternal genotype, suggesting a novel perspective on paternal contributions to the T2D predisposition.